Orienting magnetic fillers to optimize film properties

The TIPS process addresses viscosity and orientation challenges in magnetic shielding film manufacturing by rapidly aligning and locking magnetically permeable particles, enhancing magnetic properties and power transfer efficiency.

JP7618587B2Active Publication Date: 2025-01-213M INNOVATIVE PROPERTIES CO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021567910
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-15
Filing Date
2020-05-08
Publication Date
2025-01-21
Estimated Expiration
2040-05-08

AI Technical Summary

Technical Problem

Existing methods for manufacturing magnetic shielding films face challenges such as high viscosity due to high solids content, difficulty in orienting high volume mixtures of flake particles, and maintaining ordered structures during slow solvent evaporation and curing processes, leading to film deformation and disordered systems.

Method used

A method involving thermally induced phase separation (TIPS) is used to rapidly lock an ordered structure of magnetically permeable particles in a resin, applying a magnetic field for short durations to align particles, followed by phase separation and solvent removal, enhancing particle orientation and mechanical integrity.

Benefits of technology

The method results in a magnetic shielding film with improved magnetic saturation and permeability, reducing power transfer inefficiencies and film deformation, enabling faster wireless charging speeds and higher power transfer efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618587000004
    Figure 0007618587000004
  • Figure 0007618587000005
    Figure 0007618587000005
  • Figure 0007618587000006
    Figure 0007618587000006
Patent Text Reader

Abstract

A magnetic shielding film includes opposing first and second major surfaces and a plurality of particles dispersed therebetween, each particle having magnetic permeability, a thickness H along the thickness direction of the particle, a longest dimension L along the length direction of the particle perpendicular to the thickness direction of the particle, L / H being 2 or greater, the particles defining a plurality of voids therebetween, and at least 60% of the particles having their length directions oriented within 5.5 degrees of the same orientation direction.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] In some embodiments of the present disclosure, there is provided a magnetic shielding film comprising opposing first and second major surfaces and a plurality of particles dispersed therebetween, each particle having magnetic permeability, a thickness H along a thickness direction, a longest dimension L along the length direction of the particle perpendicular to the thickness direction of the particle, an L / H of 2 or greater, the particles defining a plurality of voids therebetween, and at least 60% of the particles have their length directions oriented within 5.5 degrees of the same orientation direction. [Technical field]

[0002] In some embodiments herein, about 10 4 A magnetic shielding film is provided, comprising a resin having a number average molecular weight of greater than g / mole and a plurality of anisotropically shaped particles dispersed therein at a volumetric capacity of greater than about 50%, or 55%, or 60%, or 65%, wherein at a frequency of about 1 MHz, the film has a magnetic saturation greater than about 6000 Gauss and real parts of relative magnetic permeabilities μ′1 and μ′2 along the thickness and in-plane directions of the film, respectively, such that μ′1≦5 and μ′2≧150.

[0003] In some embodiments herein, an electronic device is provided, the electronic device includes a plate configured to substantially attenuate energy contained in electromagnetic waves of a first frequency band, a receiving antenna disposed on the plate for wirelessly charging a battery disposed in the device in the first frequency band, and a magnetic shielding film disposed between the plate and the receiving antenna. The magnetic shielding film may include a plurality of anisotropically shaped particles dispersed in a resin with a volumetric capacity of more than about 50%, the particles being oriented along substantially the same direction and defining a plurality of voids therebetween, such that when the device is disposed adjacent to a transmitting antenna that transmits a power Ptx of the first frequency band to the receiving antenna, the receiving antenna receives a power Prx from the transmitting antenna, and after an increase in Prx results in an initial decrease in Prx / Ptx of at least 1%, a further increase in Prx increases Prx by at least a factor of two, since the decrease in Prx / Ptx is less than about 5%.

[0004] In some embodiments herein, a magnetic shielding film is provided that includes a resin and a plurality of anisotropically shaped particles dispersed in the resin at a volumetric capacity of greater than about 50%, wherein the resin includes a plurality of fibrous, generally parallel polymer elements that interconnect the particles, such that at a frequency of about 1 MHz, the real part of the relative permeability of the magnetic shielding film along an in-plane direction of the magnetic shielding film exceeds an amount (420.0-0.04M), where M is the magnetic saturation of the magnetic shielding film in Gauss units.

[0005] In some embodiments herein, a magnetic shielding film is provided comprising a resin and a plurality of anisotropically shaped particles dispersed in the resin at a volumetric capacity of greater than about 50%, wherein the resin comprises a plurality of fibrous, generally parallel polymer elements interconnecting the particles, thereby providing a magnetic shielding film in which the real part of the relative permeability of the magnetic shielding film along an in-plane direction of the magnetic shielding film is greater than about 130 and the magnetic saturation of the magnetic shielding film is greater than about 6,000 Gauss at a frequency of about 1 MHz.

[0006] In some aspects herein, a magnetic shielding film is provided that includes a polymeric material and a plurality of particles dispersed therein, the particles being magnetically permeable, and the polymeric material including a plurality of substantially parallel fibrous elements generally oriented along a thickness direction of the magnetic shielding film and interconnecting the plurality of particles.

[0007] In some embodiments herein, a method for producing a magnetic shielding film includes: 4 The present invention provides a method for producing a magnetic shielding film, the method comprising: providing a polymer having a number average molecular weight of greater than 1 g / mol, a diluent miscible with the polymer, and a plurality of anisotropically shaped particles having magnetic permeability; mixing the polymer, the diluent, and the plurality of anisotropically shaped particles to form a miscible solution; forming a layer of the miscible solution; applying a magnetic field to the layer to orient the particles along substantially the same orientation direction; inducing phase separation of the polymer from the diluent while the magnetic field is applied to the layer and the particles are substantially oriented along the orientation direction; and removing at least a portion of the diluent to form a magnetic shielding film, wherein at least 60% of the particles are oriented within 5 degrees of the orientation direction. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a process flow diagram of a prior art film formation and densification process. [Figure 2A] The main processing elements for the film formation and densification process according to one embodiment of the present disclosure are described. [Figure 2B] FIG. 2 is a close-up view of a magnet assembly used in a film-forming process according to an embodiment herein. [Figure 3A] 1 provides examples of particle shapes for use in the film formation and densification process according to one embodiment of the present disclosure. [Figure 3B] 1 provides examples of particle shapes for use in the film formation and densification process according to one embodiment of the present disclosure. [Figure 3C]1 provides examples of particle shapes for use in the film formation and densification process according to one embodiment of the present disclosure. [Figure 3D] 1 provides examples of particle shapes for use in the film formation and densification process according to one embodiment of the present disclosure. [Figure 4] 1 illustrates a magnetic shielding film according to an embodiment of the present disclosure. [Figure 5A] 1 provides information comparing films made by a film formation process using magnetic alignment and ultrasonic densification according to one embodiment herein compared to typical prior art films. [Figure 5B] 1 provides information comparing films made by a film formation process using magnetic alignment and ultrasonic densification according to one embodiment herein compared to typical prior art films. [Figure 5C] 1 provides information comparing films made by a film formation process using magnetic alignment and ultrasonic densification according to one embodiment herein compared to typical prior art films. [Figure 6A] 1 provides information comparing films made by a film-forming process using ultrasonic densification according to one embodiment herein compared to typical prior art films. [Figure 6B] 1 provides information comparing films made by a film-forming process using ultrasonic densification according to one embodiment herein compared to typical prior art films. [Figure 6C] 1 provides information comparing films made by a film-forming process using ultrasonic densification according to one embodiment herein compared to typical prior art films. [Figure 7A] 1 provides information comparing films made by a film-forming process using calendaring, according to one embodiment herein, compared to typical prior art films. [Figure 7B]1 provides information comparing films made by a film-forming process using calendaring, according to one embodiment herein, compared to typical prior art films. [Figure 7C] 1 provides information comparing films made by a film-forming process using calendaring, according to one embodiment herein, compared to typical prior art films. [Figure 8A] 1 provides information comparing films made by a film formation process using magnetic alignment and no ultrasonic densification in accordance with one embodiment herein compared to typical prior art films. [Figure 8B] 1 provides information comparing films made by a film formation process using magnetic alignment and no ultrasonic densification in accordance with one embodiment herein compared to typical prior art films. [Figure 8C] 1 provides information comparing films made by a film formation process using magnetic alignment and no ultrasonic densification in accordance with one embodiment herein compared to typical prior art films. [Figure 9] 1 is a graph plotting relative magnetic permeability versus magnetic saturation induction for a magnetic shielding film according to an embodiment herein. [Figure 10] 1 is a graph plotting wireless power transfer efficiency versus received power values ​​for a magnetic shielding film according to an embodiment herein. [Figure 11] 1 is a perspective view of an electronic device using a magnetic shielding film according to an embodiment of the present disclosure. [Figure 12] FIG. 2 is a flow diagram of a method for manufacturing a magnetic shielding film according to an embodiment herein. [Figure 13] 1 is a table illustrating the experimental performance of four exemplary magnetic shielding films, according to an embodiment herein. [Figure 14] FIG. 1 is a Pareto diagram illustrating the effect of various design parameters on the magnetic permeability of an exemplary magnetic shielding film, according to an embodiment herein. [Figure 15] 1 is a cube plot illustrating the effect of various design parameters on the magnetic permeability of an example magnetic shielding film, according to an embodiment herein. [Figure 16] 1 is a plot illustrating the effect of various design parameters on the magnetic permeability of an example magnetic shielding film, according to an embodiment herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In the following description, reference is made to the accompanying drawings which form a part hereof, and in which various embodiments are shown by way of illustration. The drawings are not necessarily to scale. It is to be understood that other embodiments are contemplated and may be made without departing from the scope or spirit of the specification. Accordingly, the following detailed description is not to be taken in a limiting sense.

[0010] Magnetic shielding films may be formed from highly filled composites having magnetic flake-shaped or rod-like filler particles bound together by a suitable resin. For best results, such composites should have the following characteristics: (1) a large percentage (greater than 60% by volume) of flake-shaped or elongated filler particles to maximize magnetic saturation induction, and (2) a high degree of particle orientation that is flush with the film surface to maximize magnetic permeability and promote high packing density while limiting damage to the mechanically sensitive filler particles. This leads to more effective shielding and higher power transfer efficiency. In addition, ideally the composite should have a minimal void volume fraction with sufficient binder volume fraction to provide good mechanical integrity. High saturation induction leads to faster wireless charging speeds in end-use applications.

[0011] There are several inherent challenges that must be overcome to achieve this composite. For example, mixtures with high solids contents tend to have high viscosities and can be difficult to process. In addition, orienting mixtures with high flake particle contents is difficult due to steric interactions of the solid particles. Finally, once the desired structure has been created, through any means, the structure must then be "locked" in place.

[0012] Prior art has attempted to address these challenges by performing film formation and orientation of the flakes in a relatively fluid state where the flakes have sufficient mobility. For example, this can be accomplished by creating a fluid mixture by diluting with a solvent and / or low molecular weight reactive resin, forming a film, applying a magnetic field to the film to help orient the magnetic flakes internally (creating an oriented structure), and locking the structure in place by evaporating the solvent and / or hardening the resin matrix.

[0013] However, these prior art approaches have several deficiencies that must be addressed. For example, solvent evaporation and hardening are relatively gradual (slow) processes during which the ordered system becomes disordered by normal mechanical handling and vibration. Also, although continuous application of a magnetic field while the film is in a transient state may help maintain the orientational order, it may also cause undesirable film deformation due to physical displacement of the semi-liquid material or separation of the magnetic flakes from the relatively liquefied polymer / diluent.

[0014] A new method of making magnetic shielding films is presented that addresses and overcomes these challenges. The method addresses these challenges by applying an orienting magnetic field to the magnetic shielding film for a relatively short period of time and then using a first order phase transition to rapidly lock the ordered structure in place. In some embodiments, the first order phase transition is a thermally induced phase separation (i.e., TIPS) from a single polymer / diluent gel phase to a two-phase system. In the TIPS process, the polymer forms a strong separate phase in seconds, which has a microfibrillar structure that connects the elongated magnetic particles to a network structure within a continuous diluent phase. In some embodiments, the diluent is of low volatility and can be readily extracted without disturbing the highly ordered flake arrangement, either in-line or in an off-line process that occurs at some point after film formation. In some embodiments, once the diluent is extracted, the void volume can be removed by a densification process. The methods described herein are based on and offer improvements over the film formation and densification processes described in U.S. Pat. No. 10,287,413, the entirety of which is incorporated herein by reference. The process is usually best described as a series of processes involving high filler loadings in combination with a thermally induced phase separation (TIPS) process.

[0015] FIG. 1 provides an overview of a typical process sequence for film formation and densification processes as described above. In process step A, particles 10, diluent (solvent) 12, and binder polymer 14 are mixed in a dispersion at room temperature. Examples of particles 10 used in a typical film formation process typically include acoustically active particles, soft magnetic particles, thermally conductive particles, thermally insulating particles, intumescent particles, functional particles, dielectric particles, indicator particles, polar solvent soluble particles, polar solvent swellable particles, or heat absorbing particles. However, for obvious reasons, the new films and methods described herein will use elongated magnetic particles. In process step B, particles 10, binder polymer 14, and diluent 12 are actively mixed at elevated temperature to dissolve the polymer 14 and diluent 12. In some embodiments, the blend can then be formed into a desired shape factor, either by hot pressing the mixture (e.g., on a laboratory scale) or by extruding through a heated die (e.g., on a large or manufacturing scale).

[0016] The hot film is then quenched to a lower temperature at which phase separation occurs in process step C. After inducing phase separation, at least a portion of the solvent is removed from the polymer composite in process step D, thereby forming a polymer composite sheet having a thermoplastic polymer, network structure, and particulate material distributed within the thermoplastic polymer, network structure. In some embodiments, the solvent can be removed by evaporation, with solvents having high vapor pressures being particularly suited to this removal method.

[0017] After inducing phase separation and removing at least a portion of the diluent 12, the formed thermoplastic polymer network structure may, in some embodiments, be stretched (process step E) and / or compressed (process step F) to densify the polymer composite. This can be accomplished by applying at least one of a compressive force and a tensile force to the polymer composite. In some embodiments, the method for making the polymer composite further includes, after the step of removing the solvent, applying at least one of a compressive force and a tensile force, thereby densifying the polymer composite sheet. The at least one of the compressive force and the tensile force can be applied by techniques known in the art. For example, the compressive force can be accomplished by passing the polymer composite, e.g., a polymer composite sheet, through the nip of a pair of nip rolls having a gap smaller than the thickness of the polymer composite, e.g., by calendering.

[0018] According to some aspects of the present specification, a magnetic field is applied during the formation of the magnetic shielding film during the phase transition process described above, and then the ordered structure thus generated is rapidly locked in place by cooling the film to create the magnetic shielding film. In some embodiments, the magnetic shielding film includes opposing first and second major surfaces and a plurality of particles dispersed therebetween, each particle having magnetic permeability (i.e., the ability of the magnetic material to support the generation of a magnetic field). In some embodiments, each particle can have a thickness H along the thickness direction of the particle and a longest dimension L along the length direction of the particle perpendicular to the thickness direction such that the ratio L / H is 2 or greater. In some embodiments, the length directions of at least 60% of the particles in the magnetic shielding film are oriented (i.e., aligned in substantially the same direction) within 5.5 degrees, or within 5 degrees, or within 4.5 degrees, or within 4 degrees of the same orientation direction.

[0019] In some embodiments, the orientation direction may be substantially parallel to the first and second major surfaces. In some embodiments, the particles define a plurality of voids therebetween. In some embodiments, at least some of the voids of the plurality of voids may be interconnected.

[0020] In some embodiments, the magnetic shielding film may further include a resin disposed between the first and second major surfaces, wherein the plurality of particles are dispersed in the resin. In some embodiments, the resin is about 10 4 In some embodiments, the resin may have a number average molecular weight of about 10 7 It may be less than g / mol.

[0021] In some embodiments of the magnetic shielding film, in a cross section of the magnetic shielding film taken in a vertical direction substantially perpendicular to at least one of the first and second major surfaces, the magnetic shielding film may include a plurality of pairs of vertically adjacent particles, and a plurality of substantially parallel elongated polymer elements connect the particles in each of the pairs of vertically adjacent particles. In some embodiments, the substantially parallel elongated polymer elements may be thermoplastic fibrils, which may directly attach to adjacent particles and act as a binder. In some embodiments, the substantially parallel elongated polymer elements connecting adjacent particles are substantially oriented along the vertical direction (i.e., substantially perpendicular to the orientation direction of the particles or substantially perpendicular to the first and second major surfaces). In some embodiments, the elongated polymer elements may include polyethylene.

[0022] In some embodiments, the magnetic shielding film may have real parts of relative magnetic permeabilities μ′1 and μ′2 along the thickness and in-plane directions, respectively, of the film, such that the ratio μ′2 / μ′1 at a frequency of about 1 MHz is greater than or equal to 100. In some embodiments, μ′1 of the magnetic shielding film at about 1 MHz may be less than or equal to about 5.

[0023] In some embodiments, the particles may be dispersed between the first and second major surfaces of the magnetic shielding film in a volumetric capacity of greater than about 50 percent. In some embodiments, the particles may include flakes (i.e., like thin, flat bits of material, having a thickness substantially less than the length and width of the particle). In some embodiments, the particles may have an average thickness ranging from about 0.5 microns to about 5 microns, and an average longest dimension ranging from about 20 microns to about 200 microns. In some embodiments, the particles may be substantially rod-shaped. In some embodiments, the particles may be substantially disk-shaped. In some embodiments, the particles may be spheroidal. In some embodiments, the particles may have an inner portion of lower thermal conductivity and an outer portion of higher thermal conductivity. In some embodiments, the particles may have a thermally conductive coating on their outermost surface.

[0024] In some embodiments, the particles may be ferromagnetic materials. In some embodiments, the particles may include one or more of the following materials, but are not limited to: iron, silicon, aluminum, chromium, nickel, copper, cobalt, and molybdenum. In some embodiments, the particles may include a magnetic coating, and the uncoated particles may or may not be magnetically permeable themselves. In some embodiments, the particles may be thermally conductive. In some embodiments, the magnetic shielding film may have an average thermal conductivity of at least 0.15 W / (m·K), or at least 0.2 W / (m·K), or at least 0.25 W / (m·K) along the thickness direction of the magnetic shielding film. In some embodiments, the magnetic shielding film may have an average thermal conductivity of at least 5 W / (m·K), or at least 7 W / (m·K), or at least 9 W / (m·K), or at least 10 W / (m·K), or at least 10.6 W / (m·K) along the in-plane direction of the magnetic shielding film.

[0025] According to some embodiments of the present invention, the magnetic shielding film may include a resin, and the resin may be about 104 A magnetic shielding film having a number average molecular weight of more than g / mol and a plurality of anisotropically shaped particles (e.g., elongated such that a first dimension of the particles is significantly larger than a second dimension) dispersed therein at a high volumetric capacity (e.g., greater than about 50%, or 55%, or 60%, or 65%) at a frequency of about 1 MHz. In some embodiments, the magnetic shielding film may have a magnetic saturation (i.e., a state where an increase in an applied external magnetic field no longer causes an increase in the magnetization of the film) of more than about 6000 Gauss, and the real parts of the relative magnetic permeabilities μ′1 and μ′2 along the thickness and in-plane directions, respectively, of the film, such that μ′1 is about 5 or less and μ′2 is about 150 or more. In some embodiments, the resin may include a plurality of fibrous, generally parallel polymer elements (e.g., thermoplastic fibrils) interconnecting the particles.

[0026] In some embodiments of the magnetic shielding film, at least a portion of the anisotropically shaped particles are configured to generate a magnetic moment (i.e., defining a measure of the magnetic strength and orientation of the particles, or the tendency of the particles to align with a magnetic field) in response to a magnetic field. In some embodiments, at least a portion of the anisotropically shaped particles may include a permanent magnetic moment. In some embodiments, at least a portion of the anisotropically shaped particles are magnetically conductive and electrically insulating.

[0027] In some embodiments, the resin may be a thermoplastic polymer that is formed into a network structure of the thermoplastic polymer. The thermoplastic polymer is not particularly limited. In some embodiments, the thermoplastic polymer includes at least one of, but is not limited to, polyurethanes, polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, and polylactic acid), polyamides (e.g., nylon 6, nylon 6,6, and polypeptides), polyethers (polyethylene oxide and polypropylene oxide), polycarbonates (bisphenol-A-polycarbonate), polyimides, polysulfones, polyphenylene oxides, polyacrylates (e.g., thermoplastic polymers formed from the addition polymerization of monomers containing acrylate functional groups), polymethacrylates (e.g., thermoplastic polymers formed from the addition polymerization of monomers containing methacrylate functional groups), polyolefins (polyethylene and polypropylene), styrene and styrenic random and block copolymers, chlorinated polymers (polyvinyl chloride), fluorinated polymers (polyvinylidene fluoride; polymers of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride; copolymers of ethylene, tetrafluoroethylene, and hexafluoropropylene; and polytetrafluoroethylene), and copolymers of ethylene and chlorotrifluoroethylene. In some embodiments, the thermoplastic polymer may be at least one of a homopolymer and a copolymer (e.g., a block copolymer or a random copolymer). In some embodiments, the thermoplastic polymer is a mixture of two or more thermoplastic polymers (e.g., a mixture of polyethylene and polypropylene or a mixture of polyethylene and polyacrylate). In some embodiments, the polymer may be at least one of polyethylene (e.g., ultra-high molecular weight polyethylene), polypropylene (e.g., ultra-high molecular weight polypropylene), polylactic acid, poly(ethylene-co-chlorotrifluoroethylene), and polyvinylidene fluoride. In some embodiments, the thermoplastic polymer is a single thermoplastic polymer, i.e., not a mixture of two or more thermoplastic polymers.

[0028] The molecular weight of the thermoplastic polymer is not particularly limited, except that it must have a molecular weight sufficient to be capable of phase separation from the solvent and to result in the formation of a network structure. Generally, the number average molecular weight of the thermoplastic polymer is in the range of 10 4 In some embodiments, a thermoplastic polymer having an ultra-high molecular weight may need to have a molecular weight of at least 3×10 g / mol or more. 6 A thermoplastic polymer is defined as a thermoplastic polymer having a number average molecular weight of 100 g / mol. The number average molecular weight can be measured by techniques known in the art, including, but not limited to, gel permeation chromatography (GPC). GPC can be performed in a good solvent for the thermoplastic polymer with the use of narrow molecular weight distribution polymer standards, such as narrow molecular weight distribution polystyrene standards. Thermoplastic polymers are generally characterized as being partially crystalline and exhibit a melting point. In some embodiments, the thermoplastic polymer may have a melting point between 120°C and 350°C, between 120°C and 300°C, between 120°C and 250°C, or even between 120°C and 200°C. The melting point of a thermoplastic polymer can be measured by techniques known in the art, including, but not limited to, measuring the onset temperature in a differential scanning calorimetry (DSC) test using a sample of 5 mg to 10 mg and performed at a heating scan rate of 10°C / min while the sample is under a nitrogen atmosphere.

[0029] In some embodiments, a thermoplastic polymer can be formed into a thermoplastic polymer network structure through a process that includes mixing a thermoplastic polymer with a suitable solvent to form a miscible thermoplastic polymer solvent solution, followed by phase separation of the thermoplastic polymer from the solvent, and then removing at least a portion of the solvent. This process is typically carried out by adding a particulate material to the miscible polymer solvent solution prior to phase separation. In some embodiments, the particulate material can be ferromagnetic particles. A thermoplastic polymer network structure can be formed during the phase separation step of this process. In some embodiments, a thermoplastic polymer network structure is produced by induced phase separation of a miscible thermoplastic polymer solvent solution. The thermoplastic polymer network structure is porous (i.e., pores) in nature. The pores can be continuous, which allows fluid communication from the interior region of the thermoplastic polymer network structure to the surface of the thermoplastic polymer network structure and / or between a first surface of the thermoplastic polymer network structure and an opposite second surface of the thermoplastic polymer network structure.

[0030] The pore size of the thermoplastic polymer network structure is not particularly limited. In some embodiments, the pore size is in the micrometer scale (i.e., about 1 micrometer to 1000 micrometers). In some embodiments, the pore size is in the nanometer scale (i.e., about 10 nanometers to 1000 nanometers). In some embodiments, the average pore size or median pore size P of the thermoplastic polymer network structure is 10 nanometers to 1000 micrometers, 10 nanometers to 500 micrometers, 10 nanometers to 250 micrometers, 10 nanometers to 100 micrometers, 10 nanometers to 50 micrometers, 10 nanometers to 25 micrometers, 100 nanometers to 1000 micrometers, 50 nanometers to 1000 micrometers, 50 nanometers to 500 micrometers, 50 nanometers to 250 micrometers, 50 nanometers to 100 micrometers, 50 nanometers to 50 micrometers. 100 nanometers, 50 nanometers to 25 micrometers, 100 nanometers to 1000 micrometers, 100 nanometers to 500 micrometers, 100 nanometers to 250 micrometers, 100 nanometers to 100 micrometers, 100 nanometers to 50 micrometers, 100 nanometers to 25 micrometers, 250 nanometers to 1000 micrometers, 250 nanometers to 500 micrometers, 250 nanometers to 250 micrometers, 250 nanometers to 100 micrometers, 250 nanometers to 50 micrometers, or even 250 nanometers to 25 micrometers. Conventional pore size analysis techniques can be used to statistically analyze pore sizes and pore size distributions, including imaging of cross sections (e.g., optical microscopes, scanning electron microscopes, or atomic force microscopes) and image analysis using appropriate software. Additionally, X-ray microtomography and mercury porosimetry, bubble point and capillary flow porosimetry can be used to analyze the pore size and / or pore size distribution. The continuous nature of the pores in the thermoplastic polymer network can facilitate the removal of solvent from the thermoplastic polymer network.In the present disclosure, the term "thermoplastic polymer network structure" essentially means that at least a portion of the pores of the thermoplastic polymer network structure are free of liquids and solids (e.g., contain one or more gases such as air). In some embodiments, 10 volume percent to 100 volume percent, 30 volume percent to 100 volume percent, 50 volume percent to 100 volume percent, 60 volume percent to 100 volume percent, 70 volume percent to 100 volume percent, 80 volume percent to 100 volume percent, 90 volume percent to 100 volume percent, 95 volume percent to 100 volume percent, or even 98 volume percent to 100 volume percent of the pores of the thermoplastic polymer network structure are free of liquids and solids (e.g., contain one or more gases such as air).

[0031] To form a miscible thermoplastic polymer solvent solution, the solvent is required to dissolve the thermoplastic polymer. Thus, the solvent for a particular thermoplastic polymer is selected based on this requirement. The thermoplastic polymer solvent mixture may be heated to promote dissolution of the thermoplastic polymer in the solvent. After phase separation of the thermoplastic polymer from the solvent, at least a portion of the solvent is removed from the network structure of the thermoplastic polymer using techniques known in the art, including evaporation of the solvent or extraction of the solvent with a second solvent with a lower vapor pressure followed by evaporation of the second solvent. In some embodiments, at least 10 weight percent to 100 weight percent, at least 30 weight percent to 100 weight percent, at least 50 weight percent to 100 weight percent, at least 60 weight percent to 100 weight percent, at least 70 weight percent to 100 weight percent, at least 80 weight percent to 100 weight percent, at least 90 weight percent to 100 weight percent, at least 95 weight percent to 100 weight percent, or even at least 98 weight percent to 100 weight percent of the solvent and second solvent (if used) are removed from the thermoplastic polymer network structure.

[0032] According to some aspects of the present specification, an electronic device (e.g., a wireless charging system) may include a plate configured to substantially attenuate energy contained in an electromagnetic wave of a first frequency band, a receiving antenna disposed on the plate for wirelessly charging a battery disposed in the device in the first frequency band, and a magnetic shielding film disposed between the plate and the receiving antenna. In some embodiments, the plate can attenuate the energy contained in the electromagnetic wave by absorbing the energy. In some embodiments, the magnetic shielding film may include a plurality of anisotropically shaped particles (e.g., flake-like or rod-like particles, or particles longer in a first direction than in a second direction perpendicular to the first direction) dispersed in a resin at a volumetric capacity of more than about 50%. In some embodiments, the particles may be oriented along substantially the same direction and may define a plurality of voids therebetween. In some embodiments, at least a portion of the voids may be interconnected.

[0033] In some embodiments, when the device is placed adjacent to a transmitting antenna that transmits a power Ptx of a first frequency band to the receiving antenna, the receiving antenna receives a power Prx from the transmitting antenna, and after an increase in Prx results in an initial decrease in Prx / Ptx of at least 1%, a further increase in Prx may result in a decrease in Prx / Ptx of less than about 5%, and Prx increases by at least a factor of two. In some embodiments, for an increase in Prx that results in an initial decrease in Prx / Ptx of at least 1%, Prx increases from an initial value of at least 5 watts. For purposes of this specification, the phrase "first frequency band" is intended to represent any suitable frequency band that can be wirelessly transmitted using power, and is not meant to be limiting.

[0034] According to some aspects of the present disclosure, there is provided a magnetic shielding film comprising a resin and a plurality of anisotropically shaped particles dispersed in the resin at a volumetric capacity of more than about 50%. In some embodiments, the resin may include a plurality of fibrous, generally parallel polymer elements interconnecting the particles, such that at a frequency of about 1 MHz, the real part of the relative magnetic permeability of the magnetic shielding film along the in-plane direction of the magnetic shielding film exceeds an amount (420.0-0.04M), where M is the magnetic saturation of the magnetic shielding film in Gauss units. In some embodiments, the particles have a magnetic permeability of more than about 10, more than about 50, or more than about 100. In some embodiments, the fibrous, generally parallel polymer elements may be thermoplastic fibrils, which may directly attach to the dispersed particles and act as a binder.

[0035] According to some aspects of the present disclosure, there is provided a magnetic shielding film comprising a resin and a plurality of anisotropically shaped particles dispersed in the resin at a volumetric capacity of greater than about 50%. In some embodiments, the resin may comprise a plurality of fibrous, generally parallel polymer elements interconnecting the particles, such that at a frequency of about 1 MHz, the real part of the relative permeability of the magnetic shielding film along an in-plane direction of the magnetic shielding film is greater than about 130 and the magnetic saturation of the magnetic shielding film is greater than about 6,000 Gauss.

[0036] According to some aspects of the present disclosure, there is provided a magnetic shielding film including a polymeric material and a plurality of particles dispersed therein, the particles being magnetically permeable. In some embodiments, the polymeric material may include a plurality of substantially parallel fibrous elements (e.g., fibrils) generally oriented along a thickness direction of the magnetic shielding film and interconnecting the plurality of particles.

[0037] According to some embodiments of the present disclosure, there is provided a method for producing a magnetic shielding film, comprising the steps of: 4 g / mol, or about 10 5 g / mol, or about 10 6The present invention provides a method for producing a magnetic shielding film, the method comprising: providing a polymer having a number average molecular weight of greater than 1 g / mol, a diluent miscible with the polymer, and a plurality of anisotropically shaped particles having magnetic permeability; mixing the polymer, the diluent, and the plurality of anisotropically shaped particles to form a miscible solution; forming a layer of the miscible solution; applying a magnetic field to the layer to orient the particles along substantially the same orientation direction; inducing phase separation of the polymer from the diluent while the magnetic field is applied to the layer and the particles are substantially oriented along the orientation direction; and removing at least a portion of the diluent to form a magnetic shielding film, wherein at least 60% of the particles are oriented within 5 degrees of the orientation direction.

[0038] In some embodiments, removing at least a portion of the diluent results in an intermediate magnetic shielding film, and the method further includes increasing a volumetric capacity of the particles in the intermediate magnetic shielding film to form the magnetic shielding film. In some embodiments, the volumetric capacity is increased by subjecting the polymer to vibrational energy and a compressive force. In some embodiments, the vibrational energy is ultrasonic energy. In some embodiments, at least 50% of the particles in the intermediate magnetic shielding film are oriented within 5-20 degrees of the orientation direction. In some embodiments, at least 60% of the particles in the intermediate magnetic shielding film are oriented within 5-20 degrees of the orientation direction. In some embodiments, at least 50% of the particles in the intermediate magnetic shielding film are oriented within 5-15 degrees of the orientation direction.

[0039] Returning to the drawing, FIG. 2A illustrates the main processing elements for a film formation and densification process using magnetic alignment, which builds upon the film formation process outlined in FIG. 1. In some embodiments, one or more material extruders 50 are used to mix the raw materials. In some embodiments, the raw materials are mixed in a 3000 rpm, ... 4The composition may include a polymer having an average molecular weight of g / mol, a diluent (e.g., a solvent) miscible with the polymer, and a plurality of anisotropically shaped particles having magnetic permeability. As used herein, "miscibility" refers to the ability of substances to mix in all proportions to form a solution (i.e., completely dissolve in each other at any concentration). In some solvent-polymer systems, heat may be required for the polymer to be miscible with the solvent. In contrast, substances are immiscible if they do not form a solution in significant proportions. For example, butanone is significantly soluble in water, but these two solvents are not miscible because they are not soluble in all proportions. In some cases, a component is a solvent for the polymer at higher temperatures but not at lower temperatures. At high temperatures, the polymer and the component form a miscible polymer-solvent solution. When the temperature is reduced, the component is no longer a solvent for the polymer, and the polymer may then phase separate from the component to form a polymer network. When the phase transition is induced by a change in temperature, the phase separation may be referred to as a thermally induced phase separation (TIPS) process.

[0040] In some embodiments, two extruders 50 may be used. For example, the raw materials may be mixed in a first extruder 50, and then further mixing occurs in a second extruder to achieve the final diluent concentration. In some embodiments, instead of two extruders 50, a single larger extruder 50 that allows for sufficient mixing may be used. In some embodiments, any suitable number of extruders may be used.

[0041] In some embodiments, after the miscible solution is formed in the extruder 50, the solution passes through an extrusion die 52 where it is extruded through a slit into a flattened form before passing through a casting drum 56 where it is quenched and cast into a film. In some embodiments, prior to passing through the casting drum 56, the flattened solution passes between a magnetic field generated by a magnetic component 54, and the anisotropically shaped particles contained within the formed film are oriented (i.e., aligned) along substantially the same orientation direction. That is, the particles are pulled by the magnetic field to align in the same direction. In some embodiments, that same direction can be substantially parallel to the film (i.e., aligned with the direction of travel of the film as it passes through the system). In some embodiments, the same direction can be substantially perpendicular to the film. In some embodiments, the direction of alignment (i.e., the same direction) can be in any suitable direction. In some embodiments, the solution can be dispensed onto a carrier film (e.g., a polyethylene terephthalate, or PET, liner) 55 that carries the solution through the following process steps.

[0042] While the magnetic field is still applied, phase separation is induced as the film passes through a casting drum 56, separating the polymer from the diluent and locking the aligned particles in place. In some embodiments, after the film has solidified, the diluent can be extracted in an in-line oil extraction process 58. In some embodiments, the diluent can be extracted in a separate offline system. In some embodiments, after the diluent is extracted from the film, the film may be densified (not shown). In some embodiments, densification is done using vibrational energy (e.g., ultrasonic energy). Densifying the film may increase the magnetic saturation induction properties of the film.

[0043] FIG. 2B is a close-up view of the magnet assembly used in the film-forming embodiment shown in FIG. 2A. Note that the magnet assembly is shown in FIG. 2B in a different orientation than in FIG. 2A. The magnetic components 54 are mounted with a U-shaped skid plate 57. The positions of the skid plate 57 and the magnetic components 54 (distances labeled A, B, C, D, and E) are calculated to generate the desired magnetic field strength, orientation, and position to properly align the particles in the film. The film is placed on the lower skid plate 57 (shown on the left side of FIG. 2B), and thus the position of this skid plate 57 is determined so that the film passing over its surface is in an optimal position within the generated magnetic field (e.g., approximately equidistant from the upper and lower magnetic components 54).

[0044] In some embodiments, the magnetic component 54 may be a permanent magnet. In some embodiments, the magnetic component 54 may be an electromagnet. In some embodiments, a north-facing north pole configuration (i.e., the north pole of the upper magnet faces the north pole of the lower magnet as shown in FIG. 2A) may be used to generate a substantially planar magnetic field at the location of the lower skid plate 57. In other embodiments, a south-facing south pole configuration may be used.

[0045] The particles used in the film-forming process embodiments herein may be anisotropically shaped; that is, they are longer in at least one dimension and then they are in at least one other dimension. This allows particles exhibiting a magnetic moment to be aligned in the presence of a magnetic field (i.e., allowing the longest dimension of the particle to be substantially aligned with an applied planar magnetic field). Figures 3A-3D provide some examples of particle shapes that may be used in the film-forming and densification process embodiments herein. These examples are for illustrative purposes and are not intended to be limiting. Figure 3A shows particles exhibiting a flat flake shape. In some embodiments, flake-shaped particles may be aligned in a planar magnetic field such that the plane of the flake is parallel to the magnetic field. Figure 3B shows particles exhibiting a cylindrical or rod shape. Figure 3C shows disk-shaped particles and Figure 3D shows spherical particles. Images shown in subsequent figures herein use flake-shaped particles similar to those shown in Figure 3A. However, any suitable anisotropically shaped particles having similar effects may be used.

[0046] FIG. 4 provides a cross-sectional image of a magnetic shielding film made from one embodiment of the film-forming method herein. In some embodiments, the magnetic shielding film may include a number of anisotropically shaped particles 60 (e.g., flakes) that are magnetically permeable (i.e., capable of supporting a magnetic field) and may be separated by a number of voids 62. In some embodiments, pairs of vertically adjacent particles 60 may be connected to each other by substantially parallel elongated polymer elements (i.e., polymer fibrils) 64. In some embodiments, the elongated polymer elements 64 may be substantially vertically oriented (i.e., substantially perpendicular to the orientation direction of the particles 60). Each particle 60 (such as the exemplary particle 60a in FIG. 4) has a thickness H along the thickness direction of the particle and a longest dimension L along the length direction of the particle perpendicular to the thickness direction. In some embodiments, the ratio of L / H may be about 2 or more, or about 4 or more, or about 6 or more. In some embodiments, the length directions of at least 60%, or at least 70%, or at least 80% of the particles can be oriented within 5.5 degrees of the same orientation direction (e.g., aligned substantially parallel to the length direction of the magnetic shielding film).

[0047] Figures 5A-8C provide information comparing films made by various embodiments of the magnetic film-forming process described herein with commercially available films in the prior art. In each of the film images in Figures 5A-8C, the light colored lines represent particles (e.g., magnetic dust / flakes) or connecting polymer elements, and the dark areas represent voids between the particles (which may include binders such as polymer resins).

[0048] 5A-5C compare a film made using an embodiment of the magnetic film forming process herein using magnetic alignment and ultrasonic densification to a commercially available magnetic film of the prior art. FIG. 5A shows an image of a prior art film 70a, and FIG. 5B shows an image of a film 70b made using a process according to an embodiment of the present invention. Specifically, FIG. 5B shows a film made using a magnetic alignment process in combination with ultrasonic densification. It can be seen that the prior art film 70a in FIG. 5A has a much smaller degree of alignment (more light colored lines at angles not aligned with the film) and more voids (darker areas between adjacent grains) than the film 70b in FIG. 5B made using an embodiment of the process herein. FIG. 5C shows a comparison of the orientation distribution function of the magnetically aligned and ultrasonically densified film 74 to the prior art film 72. From this exemplary graph, it can be seen that the film 74 made by the process described herein has a much tighter and higher distribution graph (i.e., a higher percentage of grains are more closely aligned) than the prior art film 72.

[0049] 6A-6C compare a film (film 80b) made using an embodiment of a magnetic film-forming process using magnetic alignment and ultrasonic densification to a film (film 80a) made by substantially the same film-forming process but without magnetic alignment. FIG. 6A shows an image of film 80a where magnetic alignment was not used, and FIG. 6B shows an image of film 80b made using a process using magnetic alignment. Both films 80a and 80b were subjected to ultrasonic densification. The images showed that film 80a (not magnetically aligned) had a lesser degree of alignment and larger voids than film 80b (magnetically aligned). FIG. 6C presents a comparison of the orientation distribution functions of magnetically aligned and densified film 84 and film 82 that was not magnetically aligned and densified. From this exemplary graph, it can be seen that film 84 made using magnetic alignment has a much tighter and higher distribution graph (i.e., a higher percentage of grains are more closely aligned) than film 82 made without magnetic alignment.

[0050] 7A-7C compare a film made using an embodiment of a magnetic film-forming process using magnetic alignment and calendering (film 70b) to a film made by substantially the same film-forming process but without magnetic alignment (film 70a). The process used to make the images in FIGS. 7A and 7B is similar to the process used to make the images in FIGS. 6A and 6B, except that a calendering process was used to densify both films instead of ultrasonic densification. FIG. 7A shows an image of film 90a where no magnetic alignment was used, and FIG. 7B shows an image of film 90b made using a process using magnetic alignment. Both films 90a and 90b were densified by calendering. The images showed that film 90a (not magnetically aligned) had a lesser degree of alignment and larger voids than film 90b (magnetically aligned). FIG. 7C shows a comparison of the orientation distribution function of magnetically aligned and densified film 94 versus film 92 that was not magnetically aligned and densified. From this exemplary graph, it can be seen that film 94 made using magnetic alignment has a much tighter and more highly distributed graph (i.e., a higher percentage of grains are more closely aligned) than film 92 made without magnetic alignment.

[0051] Finally, Figures 8A-8C compare a film made using an embodiment of the magnetic film formation process that uses magnetic alignment and does not use a densification step (film 110b) to a film made by substantially the same film formation process but without magnetic alignment (film 110a). Figure 8A shows an image of film 110a where no magnetic alignment was used, and Figure 8B shows an image of film 110b made using a process that uses magnetic alignment. Neither film 110a nor 110b underwent densification. The images showed that film 110a (not magnetically aligned) had a lesser degree of alignment and larger voids than film 110b (magnetically aligned). Figure 8C shows a comparison of the orientation distribution function of film 114 that was magnetically aligned and not densified versus film 112 that was not magnetically aligned and not densified. From this exemplary graph, it can be seen that the film 114 produced using magnetic alignment has a much tighter and more highly distributed graph (i.e., a higher percentage of the grains are more closely aligned) than the film 112 produced without magnetic alignment.

[0052] FIG. 9 is a graph plotting relative magnetic permeability versus magnetic saturation induction for a magnetic shielding film according to one embodiment of the present disclosure. In the graph, measurements of several prior art comparative shielding films 120 are plotted against measurements of a magnetic shielding film 126 made using a method according to one or more embodiments of the present disclosure. Two boundary lines are provided on the graph to more clearly depict the difference between the prior art film results 120 and the film 126 made using the method described herein. The first boundary 122 is defined by the formula (420.0-0.04M), where M is a variable that defines the magnetic saturation value of the magnetic shielding film in Gauss units. The boundary 122 clearly divides the value of the prior art film 120 from the value of the film 126 made by the present method. That is, when measured at a frequency of about 1 MHz, the real part of the relative magnetic permeability of the magnetic shielding film 126 along the in-plane direction of the magnetic shielding film is greater than (420.0-0.04M).

[0053] A second boundary 124 defines a region in the upper right corner of the graph where the relative permeability measured at about 1 MHz is about 130 or more and the magnetic saturation induction is about 6000 Gauss or more. Values ​​measured for the prior art film 120 appear only outside the boundary region. The magnetic shielding film 126 made using the method herein resides only within the region bounded by boundary 124. That is, the magnetic shielding film 126 has been shown to exhibit magnetic saturation greater than about 6000 Gauss and has real parts of the relative permeability μ′1 and μ′2 along the thickness and in-plane directions of the film, respectively, where μ′1 is about 5 or less and μ′2 is about 150 or more, or about 140 or more, or about 130 or more.

[0054] FIG. 10 is a graph plotting wireless power transfer efficiency versus received power values ​​for a magnetic shielding film according to an embodiment herein. Values ​​are plotted for several prior art comparative films 130 versus a film 135 made using an embodiment of the method herein. The Y-axis (along the left vertical edge of the graph) represents the power transfer efficiency values ​​measured for the film. Power transfer efficiency is based on the ratio Prx / Ptx, where Ptx represents the power transmitted by the transmitting antenna of the wireless charging system and Prx represents the power received by the receiving antenna (i.e., the power actually transferred). The graph in FIG. 10 shows superior performance (higher power transfer efficiency values) at each level of received power Prx for the film 135 herein versus the prior art comparative film 130, especially at higher values ​​of Prx. As shown, after an increase in Prx results in an initial decrease in power transfer efficiency (Prx / Ptx) of at least 1%, the value of Prx / Ptx may decrease by less than about 5% in the film 135 herein as Prx is further increased such that Prx increases by at least a factor of two.

[0055] 11 is a perspective view of an electronic device using a magnetic shielding film according to an embodiment of the present specification. The electronic device 200 (e.g., a smartphone with a wireless charging system) may include a conductive plate 160 that can substantially attenuate (e.g., absorb the energy or cancel the energy with a counter magnetic field) the energy contained in the electromagnetic wave 305 transmitted by the transmitting device 300, thereby reducing the amount of power received by the receiving antenna 164. For example, in some embodiments, the conductive plate 160 may represent a metal element in the electronic device 200, such as a metal part of a battery. The electromagnetic wave 305 can induce eddy currents in the conductive plate 160, and those eddy currents can generate their own magnetic field in the conductive plate 160, which can cancel and at least partially reduce the amount of power transferred from the transmitting device 300.

[0056] In some embodiments, the electronic device 200 can include receiving electronics 168 that can condition the received energy (i.e., received power) for use in charging the battery, among other functions. In some embodiments, the electronic device 200 can also include a magnetic shielding film 162, a film 162 made in accordance with an embodiment herein (i.e., a shielding film that contains or includes substantially aligned anisotropically shaped particles). In some embodiments, the transmitting device 300 (e.g., a wireless charging pad) can include a transmitting antenna 300a and transmitter electronics 300b. In some embodiments, the presence of the magnetic shielding film 162 focuses the electromagnetic wave 305 (i.e., magnetic field) toward the receiving antenna 164, preventing the wave 305 from reaching the conductive plate 160 (preventing the induction of eddy currents in the conductive plate 160), increasing power transfer efficiency. As shown in FIG. 11, the magnetic shielding film made in accordance with an embodiment herein has been shown to provide higher power transfer efficiency and reduce charging time.

[0057] Finally, FIG. 12 is a flow diagram of a method for making a magnetic shielding film according to one embodiment herein. In step 140, a polymer as described herein, a diluent (i.e., a solvent) miscible with the polymer, and a plurality of anisotropically shaped magnetically permeable particles (e.g., particles of FIG. 3A-3D) are combined. In step 142, the polymer, diluent, and particles are combined to form a miscible solution, and in step 144, a layer is formed from the miscible solution (e.g., the miscible solution is extruded through an extrusion die to create a film layer). In step 146, a magnetic field is applied to the layer to orient (i.e., align) the particles along substantially the same orientation direction (i.e., the magnetic moments of the particles orient the particles such that their longest dimension is aligned with the applied magnetic field). In step 148, while the magnetic field is still applied to the layer, phase separation of the polymer from the diluent is induced to "lock" the particles in place while they are still aligned. In step 150, at least a portion of the diluent is extracted to form the final magnetic shielding film.

[0058] In some embodiments, an additional densification step (not shown) can be applied after or simultaneously with the extraction of the diluent. This densification can be accomplished in a variety of ways, including calendaring or introducing ultrasonic energy into the film. Densification can be used as a means to further increase the volumetric capacity of particles within the magnetic shielding film. EXAMPLES

[0059] General Extrusion Process: A continuous roll of magnetic composite was prepared using the apparatus shown in FIG. 2A. Extruder #1 was a 27 mm co-rotating twin screw (obtained under the trade designation "ZSK-25" from Werner Pfleiderer, Dusseldorf, Germany). Extruder #1 was operated at 200 rpm with the following temperature profile: Zone 1 93°C, Zone 2 104°C, Zones 3-6 193°C, Zones 7 & 8 210°C, Zone 9 221°C. Ultra-high molecular weight polyethylene (UHMW-PE) was fed into a feed funnel. Mineral oil was injected into heated Zone 2 and the particles were side stuffed into Zone 4. The melt was conveyed via heated tubing to a 25 mm co-rotating twin screw, Extruder #2 (obtained under the trade designation "ZE25x48D" from Berstorff, Munich, Germany). Extruder #2 was operated at 225 rpm with the following temperature profile: Zones 1-12 177°C. Mineral oil was injected into heated Zone 4. Gravimetric feed rates of polymer, particles, and mineral oil are shown in Table 1 and correspond to the target weight percent ratios shown in Figure 13. The molten composition was mixed homogeneously and subsequently pumped into a 2 inch wide slot film die maintained at 177°C and cast onto a heat stabilized 3 mil polyethylene terephthalate (PET) liner, then conveyed through the magnetic assembly of Figure 2B, and subsequently quenched at a speed of 1.52 m / min on a casting wheel maintained at a wheel temperature of 37°C.

[0060] [Table 1]

[0061] After the initial sample films demonstrated increased magnetic permeability due to magnetic alignment of the particles within the film, a new set of designed experiments was performed to determine the empirical relationship between permeability and several factors. These factors included the solvent loading, the weight percent of the particles within the film, and the placement of the film within the applied planar magnetic field (based at least on the location of the lower skid plate where the film rests as it moves between the magnets). In the experiments, the solvent used was mineral oil, the particles within the film were Sendust SP-85 powder (in flake form), and the polymer resin was Ultra High Molecular Weight Polyethylene (UHMW-PE) GUR® 2126. Table 2 shows the key material properties referenced herein and the measurement methods used.

[0062] [Table 2]

[0063] In the series of experiments performed, the total feed rate for each design point was kept constant. The objective was to produce films of similar thickness with similar die exit velocities (actual line speeds ranged from 4.7 to 5.5 feet per minute) to minimize compounding effects from die shear related effects. The results of this testing are summarized in Figures 13-16.

[0064] Design of Experiments (DOE) variables: 1. Oil filling 2. Particle (Sendust) to polymer ratio 3.Lower (bottom) magnetic skid plate location

[0065] Four sample films were made and measured for the experiments. Figure 13 is a table summarizing the values ​​used for each DOE variable and the measured performance of the four magnetic shielding film examples. The examples provide additional process details and show how the formulation affects the material's ability to respond to magnetic fields. Formulations that promote flake (particle) orientation show higher permeability in the plane through increased particle alignment in that direction. Unless otherwise noted, these examples had the same process conditions for the extrusion and ultrasonic densification steps.

[0066] The most important formulation differences between the four examples are: Examples 1, 2, and 4 were magnetically aligned. Example 3 had no magnetic alignment. Examples 1 and 2 have the highest oil content and are highly permeable. The main difference between Example 1 and Example 2 is the skid plate configuration. The film in Example 1 is closer to the geometric center of the magnet (i.e. closer to the center of the planar magnetic field). It has slightly higher permeability than Example 2. Example 3 has a medium oil content and no magnetic alignment. The permeability value is low, but not as low as in Example 4. Example 4 has the lowest oil content and the lowest permeability, despite being magnetically aligned. The lower permeability of Example 4 is likely caused by the influence of other factors that affect the alignment of the flakes, such as steric interactions in shear flow, which may also have a concentration dependence.

[0067] Figures 14-16 show a summary of the results of the four experiments. Figure 14 is a Pareto diagram showing the effect of various design parameters on the magnetic permeability of an exemplary magnetic shielding film. The response shown with the horizontal bars is the magnetic permeability measured at 1 MHz. Within the practical purposes of the three variables (A- Sendust weight %, B- Oil loading, C- Skid plate position), oil loading was by far the more important factor. Higher oil loading was associated with higher permeability, which would correlate with better flake alignment.

[0068] FIG. 15 is a cube plot showing the effect of various design parameters on the measured magnetic permeability (Mu) at 1 MHz for an exemplary magnetic shielding film. The width of the cube (left to right) represents the change in weight percent of sendust from 93% to 96%. The height of the cube (top to bottom) represents the change in percentage of mineral oil from 43% filled to 60% filled. The depth of the cube (from the front to the back of the cube) represents the location of the lower skid plate from -0.15 to 0 inches (corresponding to the approximate location of the film passing between the magnets), where 0 inches corresponds to the geometric center between the two magnets. The cube plot helps identify which combination of three factors leads to the highest permeability value. The measured permeability values ​​are displayed as numerical values ​​in rectangular boxes near the vertices of the cube, the center point, and one additional point (labeled with a permeability value of 225.2) at the top right corner of the cube.

[0069] FIG. 16 shows the effect of various design parameters on the magnetic permeability of an exemplary magnetic shielding film, with 12 design points (full factorial design, 2 3 16 is a plot of the fitted average of the 100% sigma-filled points (100% sigma-filled points + 4 center points). From Fig. 16 it can be seen that oil filling has a single maximum effect on the measured magnetic permeability, while skid plate position has the smallest effect.

[0070] Measurement of Example Films The following sections describe how measurements of permeability, magnetic moment, and power efficiency were completed as described herein and in the claims.

[0071] I.Static magnetic properties: Prior to magnetic measurements, the samples were cut into 6 mm disks. Magnetic hysteresis loops (MH curves) were recorded using a Lake Shore Vibrating Sample Magnetometer (VSM) 7400-S. A magnetic field H was applied in the plane of the sample. The magnetic field range was set to H = ± 4 kOe, with a saturation magnetization of 4πM. swas measured at full saturation (|H|=4 kOe). The magnetic field H was measured in steps of 0.14 Oe, and the coercive field Hc was determined in the vicinity of 4πM=0 by linear fitting based on six points.

[0072] II. Dynamic magnetic properties: The samples were cut into toroids with an outer diameter of 18 mm and an inner diameter of 6 mm. The relative permeability μ r The real part of was measured. The data was analyzed according to the Keysight manual for the 16454A.

[0073] III. Wireless Power Transfer Test: Test circuit The wireless power transfer performance is tested using the circuit described herein. A signal generator was used to provide a clean sine wave signal at 128 kHz. This signal was amplified by an RF amplifier and sent to the TX matching circuit. The voltage and current probes of the matching circuit are used to measure the power received by the TX (transmit) coil Ptx. Most of this power is then transferred to the load via the RX (receive) coil and the RX matching circuit. The power received by the load Prx is measured using another set of voltage and current probes.

[0074] b. Electrical specifications of the components · The self-resonance of the free-standing TX and RX coils must be at least 20 times the test frequency of 128kHz. · The AC resistance of the free-standing TX coil should be ≦0.1Ω and the inductance should be around 6μH. · The AC resistance of a free-standing RX coil without magnetic shielding material must be ≦0.3Ω. ·The AC resistance of the TX and RX wiring must not exceed 20mΩ. ·TX wiring inductance must be ≤ 3% and RX wiring inductance must be ≤ 2% of the inductance measured with a free-standing coil. A free-standing coil is one that has a sheet of magnetic material on only one side of the coil and is separated from any metal or magnetic elements by at least 3 times the outer diameter of the coil. The load must be selected or changed so that the real part of the impedance of the load is 7.48Ω±0.05Ω and the imaginary part of the impedance is ≦±0.01Ω. Signal generators, amplifiers, oscilloscopes, and current and voltage probes must be within the manufacturer’s specified ratings for test frequency, current and voltage amplitude, or be certified by an independent party.

[0075] c. Adjust the Rx matching circuit ·The capacitance of the RX matching circuit must be adjusted before testing. The system must be pre-assembled. The TX coil must be disconnected from the matching circuit and the impedance analyzer must be connected to the RX side, not to the load. The impedance analyzer must be calibrated at the connection point to the RX side of the circuit according to the manufacturer's manual. The RX capacitors must be selected to obtain a series LCR resonant condition (minimum total measured impedance |Z|) at the test frequency of 128 kHz. It is difficult to tune to the test frequency precisely, but the main guidance is that the phase measured by the impedance analyzer is within ±5 degrees of zero. The difference in power efficiency due to the different capacitors used to test different magnetic shielding films should not exceed 0.5%.

[0076] d. Test signal The frequency of the test signal must be set to 100 Hz (i.e., 128 kHz ± 100 Hz). To minimize uncontrolled heating, the test signal may be pulse modulated with a pulse width of 94 μs (power-on phase) and a pulse period of 10 ms (power-off phase). In this case, all TX and RX power measurements must be performed within a measurement window of approximately 16 μs when the power is in the power-on phase. The measurement window must be at least 16 μs from the rising and falling edges of the power pulse. If measurements are performed using continuous wave signals, the system components should be cooled to ensure that the temperature of the TX coil elements is ≤30°C. TX coils typically use ferrite material and therefore their performance may degrade significantly at higher temperatures. Also, the capacitors in the RX tuning circuit should be selected so that the effect of temperature on their performance is minimal (i.e. the change in measured power efficiency is ≤0.5%).

[0077] e. System Linearity System performance excluding the RX coil using the material under test should have minimal impact on signal purity within the RX power range under test. The highest harmonic of the test signal measured by the RX and TX probes should be at least 1 / 10th the amplitude (current or voltage) of the main 128kHz signal. This can be tested by selecting appropriate RX and TX coil materials that have a linear response within the tested RX power range.

[0078] f. Power measurement The measured power is

number

[0079] The total system current and voltage measurement accuracy must be ≦1%, and phase ≦1 degree. Averaging must be used to achieve a power resolution ≦0.3%.

[0080] g. RX and TX coil structure · The RX and TX coils must be flat coils made of insulated wire, with insulation thickness of 200μm or less for TX and 50μm or less for RX coils. · The RX and TX coils must be circular. · The inner and outer diameters (OD) of the TX coil must be within 30% of the inner and outer diameters of the RX coil. The TX coil must be fitted with magnetic shielding material. This material must reduce the rear magnetic field by a factor of ≥10. The magnetic shielding material must be a flat sheet with lateral dimensions of approximately 20% of the TX coil OD. · The TX coil and the RX coil must contain N turns, where 3≦N≦10. · The RX coil magnetic shielding sheet should have a lateral dimension of about 20% of the RX coil OD. The magnetic material sheet should be directly on the RX winding. An aluminum plate with thickness t ≥ 0.5 mm should be attached to the magnetic shielding sheet via adhesive with thickness ≤ 10 μm. The lateral dimensions of the aluminum plate should be like those of the magnetic shielding sheet. The final assembly is shown diagrammatically below: The RX and TX coil axes must be laterally aligned so that the measured power efficiency does not change by ≦0.3%. · The RX and TX coils should be 1.6mm apart along the coil axis.

[0081] Terms such as "about" will be understood by those of skill in the art in the context in which they are used and described herein. If the use of "about" as applied to quantities describing feature sizes, quantities, and physical properties is not clear to those of skill in the art in the context in which it is used and described herein, "about" will be understood to mean within 10 percent of a particular value. A quantity given as about a particular value may be exactly that particular value. For example, if it is not clear to those of skill in the art in the context in which it is used and described herein, an amount having a value of about 1 means that the amount has a value between 0.9 and 1.1, and the value may be 1.

[0082] Terms such as "substantially" will be understood by those of skill in the art in the context in which they are used and described herein. If the use of "substantially equal" is not clear to those of skill in the art in the context in which they are used and described herein, "substantially equal" means approximately equal when about is as above. If the use of "substantially parallel" is not clear to those of skill in the art in the context in which they are used and described herein, "substantially parallel" means within 30 degrees of parallel. Directions or surfaces described as substantially parallel to one another may, in some embodiments, be within 20 degrees of parallel, or within 10 degrees, or may be parallel or nominally parallel. If the use of "substantially aligned" is not clear to those of skill in the art in the context in which they are used and described herein, "substantially aligned" means aligned within 20% of the width of the objects being aligned. Objects described as substantially aligned may, in some embodiments, be aligned within 10% or within 5% of the width of the objects being aligned.

[0083] All references, patents, or patent applications referenced above are hereby incorporated by reference in their entirety. In the event of any inconsistency or contradiction between any portion of the incorporated reference and this application, the information in the foregoing description shall take precedence.

[0084] Descriptions of elements in a figure should be understood to apply equally to corresponding elements in other figures unless otherwise indicated. Although specific embodiments have been illustrated and described herein, those skilled in the art will appreciate that the specific embodiments illustrated and described may be replaced by various alternative and / or equivalent embodiments without departing from the scope of the present disclosure. This application is intended to cover any adaptations or variations of the specific embodiments discussed herein. Accordingly, it is intended that the present disclosure be limited only by the claims and the equivalents thereof. In addition to the above-described embodiments, the following aspects are noted. (Appendix 1) 1. A magnetic shielding film comprising opposing first and second major surfaces and a plurality of particles dispersed therebetween, each particle having magnetic permeability, a thickness H along a thickness direction of the particle, a longest dimension L along a length direction of the particle perpendicular to the thickness direction, an L / H of 2 or greater, the particles defining a plurality of voids therebetween, and at least 60% of the particles have their length directions oriented within 5.5 degrees of a same orientation direction. (Appendix 2) 2. The magnetic shielding film of claim 1, wherein the length directions of at least 60% of the particles are oriented within 5 degrees of the same orientation direction. (Appendix 3) 2. The magnetic shielding film of claim 1, wherein the length directions of at least 60% of the particles are oriented within 4.5 degrees of the same orientation direction. (Appendix 4) 2. The magnetic shielding film of claim 1, wherein the length directions of at least 60% of the particles are oriented within 4 degrees of the same orientation direction. (Appendix 5) 2. The magnetic shielding film of claim 1, wherein at least some of the voids among the plurality of voids are interconnected. (Appendix 6) 2. The magnetic shielding film of claim 1, wherein in a cross-section of the magnetic shielding film in a vertical direction substantially perpendicular to at least one of the first and second major surfaces, the magnetic shielding film includes a plurality of pairs of vertically adjacent particles, and a plurality of substantially parallel elongated polymer elements connect the particles in each of the pairs of vertically adjacent particles. (Appendix 7) 7. The magnetic shielding film of claim 6, wherein the substantially parallel elongated polymer elements connecting the particles in each of the pairs of vertically adjacent particles are substantially oriented along the vertical direction. (Appendix 8) 7. The magnetic shielding film of claim 6, wherein the elongated polymer elements comprise polyethylene. (Appendix 9) 2. The magnetic shielding film of claim 1, wherein the orientation direction is substantially parallel to the first and second main surfaces. (Appendix 10) 2. The magnetic shielding film of claim 1, wherein the particles are rod-shaped. (Appendix 11) 2. The magnetic shielding film of claim 1, wherein the particles are disk-shaped. (Appendix 12) 2. The magnetic shielding film of claim 1, wherein the particles include one or more of iron, silicon, aluminum, chromium, nickel, copper, cobalt, and molybdenum. (Appendix 13) 2. The magnetic shielding film of claim 1, wherein the particles include a magnetic coating on their outermost surface. (Appendix 14) 14. The magnetic shielding film of claim 13, wherein the uncoated particles are not magnetically permeable. (Appendix 15) 2. A magnetic shielding film as described in claim 1, having real parts of relative magnetic permeabilities μ′1 and μ′2 along the thickness and in-plane directions of the film, respectively, such that μ′2 / μ′1≧100 at a frequency of about 1 MHz. (Appendix 16) 16. The magnetic shielding film of claim 15, wherein μ′1≦5 at about 1 MHz. (Appendix 17) 2. The magnetic shielding film of claim 1, wherein the particles have an average thickness in the range of about 0.5 microns to about 5 microns and an average longest dimension in the range of about 20 microns to about 200 microns. (Appendix 18) 2. The magnetic shielding film of claim 1, wherein the particles are thermally conductive. (Appendix 19) 16. The magnetic shielding film of claim 15, having an average thermal conductivity of at least 0.15 W / (m·K), or 0.2 W / (m·K), or 0.25 W / (m·K) along a thickness direction of the magnetic shielding film. (Appendix 20) 16. The magnetic shielding film of claim 15, having an average thermal conductivity of at least 5 W / (m·K), or 7 W / (m·K), or 9 W / (m·K), or 10 W / (m·K), or 10.6 W / (m·K) along an in-plane direction of the magnetic shielding film. (Appendix 21) 2. The magnetic shielding film of claim 1, wherein the particles include an inner portion of lower thermal conductivity and an outer portion of higher thermal conductivity. (Appendix 22) 2. The magnetic shielding film of claim 1, wherein the particles include a thermally conductive coating on their outermost surface. (Appendix 23) The method further includes the steps of: providing a resin disposed between the first and second major surfaces, the plurality of particles being dispersed in the resin, the resin having a viscosity of about 1000 psi; 4 2. The magnetic shielding film of claim 1, having a number average molecular weight of more than g / mol. (Appendix 24) The number average molecular weight of the resin is about 10 7 The magnetic shielding film of claim 23, wherein the magnetic shielding film has a molecular weight of less than 100 g / mol. (Appendix 25) 2. The magnetic shielding film of claim 1, wherein the particles in the plurality of particles are dispersed between the first and second major surfaces at a volumetric capacity of greater than about 50%. (Appendix 26) about 10 4 1. A magnetic shielding film comprising a resin having a number average molecular weight of greater than about 50%, or 55%, or 60%, or 65% by volume of ... A magnetic saturation greater than about 6000 Gauss; and the real parts of relative magnetic permeabilities μ′1 and μ′2 along the thickness and in-plane directions of the film, respectively, are μ′1≦5 and μ′2≧150. (Appendix 27) 27. The magnetic shielding film of claim 26, wherein at least a portion of the anisotropically shaped particles are configured to generate a magnetic moment in response to a magnetic field. (Appendix 28) 27. The magnetic shielding film of claim 26, wherein at least a portion of the anisotropically shaped particles comprise a permanent magnetic moment. (Appendix 29) 27. The magnetic shielding film of claim 26, wherein at least a portion of the anisotropically shaped particles are magnetically conductive and electrically insulating. (Appendix 30) 27. The magnetic shielding film of claim 26, wherein the resin comprises a plurality of fibrous, generally parallel polymer elements interconnecting the particles. (Appendix 31) 1. An electronic device comprising: a plate configured to substantially attenuate energy contained in electromagnetic waves in a first frequency band; a receiving antenna disposed on the plate for wirelessly charging a battery disposed in the device within the first frequency band; a magnetic shielding film disposed between the plate and the receiving antenna, the magnetic shielding film including a plurality of anisotropically shaped particles dispersed in a resin at a volumetric capacity of greater than about 50%, the particles being oriented along substantially the same direction and defining a plurality of voids therebetween; This provides an electronic device whereby, when the device is positioned adjacent to a transmitting antenna that transmits power Ptx of the first frequency band to the receiving antenna, the receiving antenna receives power Prx from the transmitting antenna, and after an increase in Prx results in an initial decrease in Prx / Ptx of at least 1%, any further increase in Prx results in an increase of at least a factor of 2 such that the decrease in Prx / Ptx is less than about 5%. (Appendix 32) 32. The electronic device of claim 31, wherein the increase in Prx results in the initial decrease of Prx / Ptx by at least 1%, where Prx increases from an initial value of at least 5 Watts. (Appendix 33) 32. The electronic device of claim 31 , wherein at least some of the voids in the plurality of voids are interconnected. (Appendix 34) 32. The electronic device of claim 31, wherein the plate is configured to substantially attenuate the energy contained in electromagnetic waves in the first frequency band by primarily absorbing the energy. (Appendix 35) A magnetic shielding film comprising a resin and a plurality of anisotropically shaped particles dispersed in the resin at a volumetric capacity of greater than about 50%, wherein the resin comprises a plurality of fibrous, generally parallel polymer elements interconnecting the particles, such that at a frequency of about 1 MHz, the real part of the relative permeability of the magnetic shielding film along an in-plane direction of the magnetic shielding film exceeds (420.0-0.04M), where M is the magnetic saturation of the magnetic shielding film in Gauss units. (Appendix 36) 36. The magnetic shielding film of claim 35, wherein the particles have a magnetic permeability of greater than about 10. (Appendix 37) 36. The magnetic shielding film of claim 35, wherein the particles have a magnetic permeability of greater than about 50. (Appendix 38) 36. The magnetic shielding film of claim 35, wherein the particles have a magnetic permeability of greater than about 100. (Appendix 39) 1. A magnetic shielding film comprising: a resin; and a plurality of anisotropically shaped particles dispersed in the resin at a volumetric capacity of greater than about 50%, the resin comprising a plurality of fibrous, generally parallel polymer elements interconnecting the particles, such that at a frequency of about 1 MHz, a real part of a relative permeability of the magnetic shielding film along an in-plane direction of the magnetic shielding film is greater than about 130 and a magnetic saturation of the magnetic shielding film is greater than about 6,000 Gauss. (Appendix 40) 1. A magnetic shielding film comprising a polymeric material and a plurality of particles dispersed therein, the particles being magnetically permeable, the polymeric material including a plurality of substantially parallel fibrous elements generally oriented along a thickness direction of the magnetic shielding film and interconnecting the plurality of particles. (Appendix 41) A method for manufacturing a magnetic shielding film, comprising the steps of: about 10 4 providing a polymer having a number average molecular weight of greater than g / mol, a diluent miscible with said polymer, and a plurality of anisotropically shaped particles having magnetic permeability; mixing the polymer, the diluent, and the plurality of anisotropically shaped particles to form a miscible solution; forming a layer of the miscible solution; applying a magnetic field to the layer to orient the particles along substantially the same orientation direction; applying the magnetic field to the layer to induce phase separation of the polymer from the diluent while the particles are oriented substantially along the orientation direction; removing at least a portion of the diluent to form a magnetic shielding film, wherein at least 60% of the particles are oriented within 5 degrees of the orientation direction. (Appendix 42) 42. The method of claim 41, wherein removing at least a portion of the diluent results in an intermediate magnetic shielding film, the method further comprising increasing a volumetric capacity of the particles within the intermediate magnetic shielding film to form the magnetic shielding film. (Appendix 43) 43. The method of claim 42, wherein the volumetric capacity is increased by subjecting the polymer to vibrational energy and a compressive force. (Appendix 44) 44. The method of claim 43, wherein the vibrational energy comprises ultrasonic energy. (Appendix 45) 43. The method of claim 42, wherein at least 50% of the grains in the intermediate magnetic shielding film are oriented within 5 to 20 degrees of the orientation direction. (Appendix 46) 43. The method of claim 42, wherein at least 60% of the grains in the intermediate magnetic shielding film are oriented within 5 to 20 degrees of the orientation direction. (Appendix 47) 43. The method of claim 42, wherein at least 50% of the grains in the intermediate magnetic shielding film are oriented within 5 to 15 degrees of the orientation direction. (Appendix 48) The number average molecular weight of the polymer is about 10 5 g / mol or more, as described in appendix 41. (Appendix 49) The number average molecular weight of the polymer is about 10 6 g / mol or more, as described in appendix 41.

Claims

1. 1. A magnetic shielding film comprising: opposing first and second major surfaces; and a plurality of particles dispersed therebetween, each particle having magnetic permeability, a thickness H along a thickness direction of the particle, a longest dimension L along a length direction of the particle perpendicular to the thickness direction, an L / H of 2 or greater, the particles defining a plurality of voids therebetween, and at least 60% of the particles having their length directions oriented within 5.5 degrees of a same orientation direction; A magnetic shielding film, wherein in a cross-section of the magnetic shielding film in a vertical direction substantially perpendicular to at least one of the first and second major surfaces, the magnetic shielding film includes a plurality of pairs of vertically adjacent particles, and a plurality of substantially parallel elongated polymer elements connect the particles in each of the pairs of vertically adjacent particles.

2. The magnetic shielding film of claim 1 , wherein at least some of the voids of the plurality of voids are interconnected.

3. The magnetic shielding film of claim 1 , wherein the substantially parallel elongated polymer elements connecting the particles in each of the pairs of vertically adjacent particles are substantially oriented along the vertical direction.

4. The magnetic shielding film of claim 1 , wherein the elongated polymer elements comprise polyethylene.

5. The magnetic shielding film of claim 1 , wherein the particles are rod-shaped.

6. The magnetic shielding film of claim 1 , wherein the particles comprise one or more of iron, silicon, aluminum, chromium, nickel, copper, cobalt, and molybdenum.

7. The magnetic shielding film of claim 1 , wherein the particles include a magnetic coating on their outermost surface.

8. The magnetic shielding film of claim 7 , wherein the uncoated particles are not magnetically permeable.

9. 2. The magnetic shielding film of claim 1, having real parts of relative magnetic permeabilities μ'1 and μ'2 along the thickness and in-plane directions, respectively, of the film, where μ'2 / μ'1≧100 at a frequency of about 1 MHz.

10. 10. The magnetic shielding film of claim 1, wherein the particles have an average thickness in the range of about 0.5 microns to about 5 microns and an average longest dimension in the range of about 20 microns to about 200 microns.

11. 10. The magnetic shielding film of claim 9, having an average thermal conductivity of at least 0.15 W / (m·K), or 0.2 W / (m·K), or 0.25 W / (m·K) along a thickness direction of the magnetic shielding film.

12. 10. The magnetic shielding film of claim 9, having an average thermal conductivity of at least 5 W / (m·K), or 7 W / (m·K), or 9 W / (m·K), or 10 W / (m·K), or 10.6 W / (m·K) along an in-plane direction of the magnetic shielding film.

13. The method further includes the steps of: providing a resin disposed between the first and second major surfaces, the plurality of particles being dispersed in the resin, the resin having a viscosity of about 1000 psi; 4 The magnetic shielding film of claim 1 having a number average molecular weight of greater than g / mol.

14. The magnetic shielding film of claim 1 , wherein the particles in the plurality of particles are dispersed between the first and second major surfaces at a volumetric capacity of greater than about 50%.

Citation Information

Patent Citations

  • Radio wave absorber

    JP2002217586A

  • Electromagnetic wave absorbent and its manufacturing method

    JP2003229694A

  • Composite magnetic material, method for manufacturing the same, antenna, and communication device

    JP2013253122A

  • Method for manufacturing noise shield cable, and noise shield cable

    JP2017027730A

  • Composition and composite sheet for dissipating heat and shielding EMI

    KR1020170131930A